(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This main aim of this research is to know the Employee’s Perception of HR Practices followed in the organisation. The study is descriptive in nature. The objective of the study to know the employees perception towards HR practices such as perception of internal communication level of training and development performance management, to find out whether the employees are satisfied with the HR Practices followed in the organisation. The sample size is 110. The sample method used for this study is Convenience sampling method. The data has been collected through a well-structured questionnaire and has been analysed with the help of SPSS package. Percentage Analysis and Independent T test has been used to analysis the data. From the Descriptive analysis it was found that majority of the respondents are female and they belongs to the age group of 30 -40 years and they are Degree holders and they have more than two years of working experience in the organisation. From this study it was found that employees of Sarathy Export Fabrics employees were aware of their HR practices followed in the organization. HR practices implemented by the company are shared to employees by proper channels among employees; they also conduct training programs for the development of employee’s performance. The employees stated that they are satisfied with the Performance appraisal and the steps taken by the authorities for employees career Development.